Composition Design and Properties Characterization of Laser‐Cladded Ni51.6Ti34.4Cu14 Coating on AZ91D Magnesium Alloy. Issue 9 (20th April 2022) - Jiang, Lipeng; Cui, Xiufang; Jin, Guo; Zhang, Dan; Lu, Bingwen; Wen, Xin; Zhang, Xuerun; Wan, Simin
Abstract : The bottleneck challenge of laser‐cladded coating preparation of magnesium alloys is the low melting point of alloys. This greatly restricts the selection of coating material. In this article, the composition of Ni–Ti–Cu coating is designed by cluster line criterion, and the thermal properties of the coating are simulated by JMatPro software. Through the analysis of simulation results, the Ni51.6 Ti34.4 Cu14 coating is selected and successfully prepared on AZ91D magnesium alloy via laser cladding technology. Then the microstructure, wear resistance, and corrosion resistance of the coating are studied in detail. The results of X‐Ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive spectrometer (EDS), and transmission electron microscope (TEM) demonstrated that there is a good metallurgical bond between the coating and the substrate, and the coating is mainly composed of Ni3 Ti, TiNi0.8 Cu0.2, and (Cu, Ni) solid solution phases. Also, there are no obvious pores and crack defects in the coating. Remarkably, AZ91D alloy showed significant improvement in corrosion resistance and wear resistance. Among them, the wear volume of the coating is decreased by 71.9% than that of AZ91D alloy. In particular, the corrosion current density of the coating is three orders of magnitude lower than that of AZ91D alloy. Abstract : The coating of Ni–Ti–Cu is designed by cluster line criterion and thermal–physical properties simulation. The Ni51.6 Ti34.4 Cu14 coating is successfully fabricated on the surface of AZ91D magnesium alloy by laser cladding. The microstructure and properties of the coating are carefully analyzed and characterized. It provides a theoretical basis for laser cladding Ni–Ti–Cu coating on magnesium alloys.